Pengaruh Pertumbuhan Penjualan, Struktur Aset, Resiko Bisnis, dan Ukuran Perusahaan terhadap Struktur Modal dengan Profitabilitas sebagai Variabel Moderasi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Annisa Annisa; Ruswan Nurmadi (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the effect of sales growth, asset structure, business risk and company size on the capital structure with profitability as a moderation variable. The population in this study is all manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Sampling technique using purposive sampling with a sample of 62 companies with 5 years of observation so that the total observation data is 310. The data analysis technique of this study uses Multiple Linear Regression analysis and in moderating variable testing using a residual test approach. The results showed that sales growth, asset structure, and business risk had a positive and significant effect on the capital structure, the size of the company did not have a significant effect on the capital structure Profitability is able to moderate the effect of sales growth, asset structure, and business risk on capital structure, profitability is not able to moderate the effect of company size on capital structure in Manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021.